Spatial Factors Shape Taxonomic and Functional Beta‐Diversity in Water‐Filled Tree Holes in Different Biogeographical Regions - Francesca Cerroti; Thibaut Rota; Francisco Valente‐Neto; K. T. Fahis; Red Calore; Gustavo Q. Romero; Karumampoyil Sakthidas Anoop Das; Andreas Bruder; Martin M. Gossner (Ecology Letters, 2025)
A central goal in ecology is to understand the mechanisms shaping community assembly at different spatial and temporal scales. This knowledge is crucial for improving conservation strategies, but remains limited for ephemeral habitats. We investigated the contribution of environmental, that is, physical and chemical microhabitat properties, and spatial factors in shaping taxonomic and functional β‐diversity of macroinvertebrate metacommunities inhabiting water‐filled tree holes (WTHs) in forests in three biogeographical regions: Temperate‐Mediterranean (France), Neotropical (Brazil), and Palaeotropical (India). We conducted standardised surveys of 35 WTHs per region on 100 ha plots. Spatial factors had a stronger effect on taxonomic and functional β‐diversity than environmental properties. Species richness differences dominated taxonomic β‐diversity. Processes driving functional β‐diversity showed biogeographic patterns, with functional turnover being pronounced in the Palaeotropical rainforest. These findings highlight the key role of spatial processes in shaping WTH metacommunities and emphasise the need for conservation strategies that maintain habitat connectivity and old‐growth forests.